Moderat Islamic Da'wah to Eliminate Islamophobia - Sila, Muhammad Amin (Institut Agama Islam Syarifuddin Lumajang, 2022)
Islamophobia is one of the latent problems in many moslem country, including where the majority of the population is Muslim, such as Indonesia. Hatred and fear of Islam, can disturb the harmony in society. This article describes the dangers of Islamophobia, and some strategies which can be taken to handle it. The aims of this study are to explore what are the challenges and opportunities of the Indonesian people regarding these Islamophobia problems. This article uses the theory and concept of Islamophobia. In addition, the concept of discourse popularized by Jurgen Habermas is used to examine the problems. This qualitative study uses a literature approach. Based on the discussion conducted, Islamophobia in Indonesia can permeate the personalities of non-Muslims and Muslims alike. Therefore, efforts are needed to spread an understanding of the true teachings of Islam. Such efforts are the responsibility of all Muslims. One of the ways that can be taken, is echoing Islam rahmatan lil'alamin, spoken and written at every opportunity. Most importantly, practice behavior according to the noble values ​​of Islam in order to represent the goodness of Islam in front of the widest public. Keywords: Indonesia, Islam, Islamophobia, compassion, discourse